Faith Learning Integration: A Case Study of Biology, Physics, Chemistry and Mathematics Lecturers’ Teaching Practices - Meri Fuji Siahaan (Universitas Pelita Harapan, 2021)
Faculty members of a private Christian Teachers College in Tangerang have been assigned to integrate faith and learning. The purpose of this research was to describe Biology, Physics, Chemistry and Mathematics lecturers’ practices of faith learning integration on their teachings. Five lecturers including two lecturers teaching Physics, and the others each teaching Biology, Chemistry and Mathematics were involved in this research. Two student teachers contributed as well in the research. The data were derived from interview with five faculty members and collecting their course syllabus along with the interview with two student teachers. Descriptive qualitative research with a case study approach was employed. The data were described and analyzed in the light of the current literatures. The findings showed that those five faculty members have been implementing faith learning integration on their teaching with a pedagogy of transferring new information. This paper suggests faculty to go beyond faith learning integration and to focus on learning as formation of heart and desire.